2020
DOI: 10.1111/jfpe.13455
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of moderate electric field and conventional marination methods applied to chicken breast muscles

Abstract: This research aimed to compare the effect of the brine‐salting process when applying a moderate electric field (MEF) and during conventional treatment of chicken breast muscles. Chicken breasts were cut into cylindrical shapes, either longitudinally or cross‐section according to muscle fibers, with dimensions of 2 × 3 cm2. Samples were submerged in marinade solutions (salt and polyphosphate‐PO40.4em3−) at concentrations of 3, 5, and 7% at 4°C for 300 min of processing. The results showed that the mass transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Mass of the solvent, the solute, and the marinated material are the basic factors in the marination process (Moreno et al ., 2020). Figure 1 showed the variations of total mass, water content, and lactic acid content of pork during the marination process with different mass fractions of lactic acid, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Mass of the solvent, the solute, and the marinated material are the basic factors in the marination process (Moreno et al ., 2020). Figure 1 showed the variations of total mass, water content, and lactic acid content of pork during the marination process with different mass fractions of lactic acid, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, they found relatively steep slopes by directly relating the concentration of salt in the salmon samples to the salting time and achieving high final concentrations of salt in the salmon since a directly proportional relationship was observed between the equilibrium concentration and the concentration of the solution; that is, a higher brine concentration resulted in a higher salt concentration in the samples. Moreno et al (2020) studied marination applied to chicken breasts at concentrations of 3, 5, and 7% (salt and polyphosphate), and the results showed that the 7% concentration improved the mass transfer of ions in the treated samples.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon might be attributed to the selective binding of negatively charged chloride ions to MP, which led to increased repulsion force, thereby enhancing protein affinity towards water (Zheng et al, 2017). Moreno et al (2020) supposed that the decrease in cooking loss could be attributed to changes in meat protein due to the induction of brine and PEF, which could reduce protein interaction and increase WHC. In a previous report, beef soaked in calcium chloride had reduced cooking loss, which was responsible for the formation of three-dimensional reticular structures with strong contractility, and increased binding force between protein and free water (Klinhom et al, 2015).…”
Section: Improvement Of Whc and Cooking Loss In Chicken Breast Meatsmentioning
confidence: 99%